Supervisory Management in Improving School Quality (Case Study at SMAN 1 Tanjung Lago South Sumatra) - Nyoman Widiya Widana Nyoman; Tri Widayatsih; Muhammad Juliansyah Putra (Inovasi Sekolah Dasar: Jurnal Kajian Pengembangan Pendidikan, 2024)
Abstract This research aims to (1) Understand and describe the supervision of teacher attendance in schools, (2) Understand and describe the suitability of QR Codes for teacher attendance, and (3) Understand and describe the benefits of using QR Codes for attendance compared to manual attendance. This research employs a qualitative method, which is appropriate for the topic under study as the research area is one that is subject to change and development based on existing social situations. Informant selection in this research was done using the snowball sampling technique. The results of the study indicate that: (1) Although manual attendance has many drawbacks, it can still be used as a backup if the signal is lost, (2) Digital attendance is very suitable for current times because it facilitates attendance in an effective and efficient manner, and (3) The benefits of digital attendance have a positive impact and offer advantages because digital attendance is more transparent and flexible in supervision, potentially contributing to the improvement of school quality.